Rare bird documentation form for Red-necked Phalarope at Gilmore City Sewage Pond, 1979 - Cummins, Raymond L.et al (1979)
Rare bird documentation form for a Red-necked Phalarope at Gilmore City Sewage Pond in Pocahontas County, IA on September 20, 1979. Epson - sheet feed